Pengenaan Biaya Tambahan Pada Transaksi Jual Beli Di E-commerce dan Marketplace (RechtJiva, 2025)
In sales transactions through e-commerce platforms, this issue is examined from the perspective of consumer protection law in Indonesia. This issue is raised due to the absence of norms regarding price transparency and maximum limits on additional fees imposed by businesses, which has an impact on legal uncertainty for consumers. This study formulates two main problems, namely, the weakness of regulations on additional fees outside the base price in the Consumer Protection Law, and ideal alternative regulations for such practices in the context of e-commerce in Indonesia. The research method used is a legal normative approach combining legislative, conceptual, and comparative methodologies. The findings indicate that Indonesia’s legal framework has not yet specifically addressed the imposition of additional fees, despite such practices already occurring across various platforms. Article 10 of the UUPK on regulates base prices and discounts, without covering additional fees. Comparative studies with Canada and Australia show that both countries have regulated price transparency through regulations that require clarity of information and consistency between advertised prices and charged prices. Based on these findings, and ideal legal framework adapted from best practices in both countries is proposed.